PENGARUH TEKNIK PENGOLAHAN TERHADAP KUALITAS KAKI NAGA IKAN PATIN - Sirtin, Pramita; Syarif, Wirnelis; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was aims to analyze the effect of processing techniques of the quality catfish drum stick in terms of shape, colour, texture, aroma, and flavour. This type of research is pure experiment (true experimental) using the method of complete random design with three repetition. The type of the data used is the primary data sourced from 30 panelists who gave the answer to the question form (format organoleptic). The data already obtained later is tabulated in the form of tables and the analysis Variant (ANAVA). If different test followed by Duncan. The results showed significant effect on the quality the same of the shape catfish drum stick. Results of the indicator oval shape, shipshape, colour of the yellow gold, elastic texture, fragrant aroma and tasteful flavour was no significant effect of the catfish drum stick quality with the different processing techniques.Keywords : Drum Stick, Catfish, Quality.